Postoperative pain intensity associated with the use of different nickel-titanium shaping systems during single-appointment endodontic retreatment: a randomized clinical trial - Eyüboğlu, Tan Fırat; Özcan, Mutlu (Quintessence Publishing Co Inc, 2019)
Objective: The objective of this randomized clinical trial was to compare the effect of different NiTi shaping systems on postoperative pain after single-appointment nonsurgical endodontic retreatment. Method and materials: Between September 2016 and December 2016, 99 patients with asymptomatic root canal-treated teeth requiring nonsurgical endodontic retreatment were randomly divided into three groups (n = 33 per group). After removing previous root canal filling, instrumentation was performed using One Shape, Revo-S, and WaveOne systems in groups 1, 2, and 3, respectively. Postoperative pain intensity was assessed at 6, 12, 18, 24, 48, and 72 hours, 7 days, and 1 month after the retreatment. Data were analyzed using one-way ANOVA and Mann-Whitney U and Kruskal-Wallis tests alpha = .01). Results: Up to 72 hours, postoperative pain was significantly less in group 1 than in groups 2 and 3 (P < .01). From 72 hours to 7 days, postoperative pain was significantly less in groups 1 and 2 (P> .05), compared to group 3 (P < .01). At 1 month, postoperative pain was not significantly different among all three groups (P > .05). Postoperative pain was the highest with WaveOne group. Conclusions: Since One Shape and Revo-S are both based on the rotational approach and WaveOne on reciprocal approach, less incidence of postoperative pain intensity with One Shape and Revo-S in single-appointment nonsurgical endodontic retreatment could be associated with the motion type during root canal shaping.
Keywords: Continuous Rotation; Postoperative Pain; Randomized Controlled Clinical Trial; Reciprocating Motion; Retreatment; Single-Appointment Endodontic Retreatment